Preoperative Evaluation of Carotid Artery Stenosis: Comparison of Contrast-Enhanced MR Angiography and Duplex Sonography with Digital Subtraction Angiography - Borisch, Ingitha; Horn, Markus; Butz, Bernhard; Zorger, Niels; Draganski, Bogdan; Hoelscher, Thilo; Bogdahn, Ulrich; Link, Johann (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Contrast-enhanced MR angiography and extracranial color-coded duplex sonography are noninvasive, preoperative imaging modalities for evaluation of carotid artery stenosis. Innovative techniques and improvements in image quality require frequent reassessment of accuracy, reliability, and diagnostic value compared with those of digital subtraction angiography (DSA). We evaluated contrast-enhanced MR angiography and duplex sonography compared with DSA for detection of high-grade carotid artery stenoses.METHODS: Four readers, blinded to clinical symptoms and the outcome of other studies, independently evaluated stenoses on contrast-enhanced MR angiograms in 71 vessels of 39 symptomatic patients. Duplex sonography was also performed in all vessels. The severity of stenosis was defined according to North American Symptomatic Carotid Endarterectomy Trial criteria (0–29%, 30–69%, 70–99%, 100%). Results of both modalities were compared with the corresponding DSA findings.RESULTS: Contrast-enhanced MR angiography had a sensitivity and specificity of 94.9% and 79.1%, respectively, for the identification of carotid artery stenoses of 70% or greater. Sensitivity and specificity of duplex sonography were 92.9% and 81.9%, respectively. Combining data from both tests revealed a sensitivity and specificity of 100% and 81.4%, respectively, for concordant results (80% of vessels).CONCLUSION: Concordant results of contrast-enhanced MR angiography and duplex sonography increase the diagnostic sensitivity to 100%. The reliability of MR angiography is comparable to that of DSA. The combination of contrast-enhanced MR angiography and duplex sonography might be preferable over DSA for preoperative evaluation in most patients, thus reducing the risk of perioperative morbidity and improving the overall outcome.